2015
DOI: 10.7314/apjcp.2015.16.15.6749
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Matrix Metalloproteinase-2 and -9 in Patients with Laryngeal Squamous Cell Carcinoma and Clinical Significance

Abstract: Background: Laryngeal cancer is an important malignancy in head and neck area and squamous cell carcinoma (SCC) is the most common type accounting for 95% of cases. Increase in matrix metalloproteinases (MMPs) in different tumors and their correlation with tumor invasiveness has been documented. However, most studies have evaluated MMP-2 and MMP-9 expression and few have evaluated serum levels. The aim of current study was to evaluate serum levels in patients with laryngeal SCC compared to normal subjects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
4
13
0
Order By: Relevance
“…SOX2-OT-knockdown markedly reduced the expression of Bcl-2 protein, and increased the protein levels of Bax and cleaved caspase 3. In addition, it has been reported that increased expression of matrix metalloproteinases, particularly MMP-7 and MMP-9, is associated with occurrence and development of laryngeal carcinoma malignization (28)(29)(30). The present data suggested that the expression levels of MMP-7 and MMP-9 were markedly reduced by SOX2-OT-silencing.…”
Section: Discussionsupporting
confidence: 56%
“…SOX2-OT-knockdown markedly reduced the expression of Bcl-2 protein, and increased the protein levels of Bax and cleaved caspase 3. In addition, it has been reported that increased expression of matrix metalloproteinases, particularly MMP-7 and MMP-9, is associated with occurrence and development of laryngeal carcinoma malignization (28)(29)(30). The present data suggested that the expression levels of MMP-7 and MMP-9 were markedly reduced by SOX2-OT-silencing.…”
Section: Discussionsupporting
confidence: 56%
“…16 In another recent study done by Lofti A et al, where they evaluated the serum levels of MMP-2 and MMP-9 in 20 patients with OSCC and compared them to those of 20 normal subjects, both markers were found to be significantly increased in OSCC patients compared to healthy subjects. 13 The distribution of sites of OSCC among the subjects was similar to that proposed by Warnakulsuriya S., who also observed similar kind of occurrence of OSCC in their study, buccal cancer being more common among Asian populations due to betel quid/tobacco chewing habits. 5 When comparison was made based on the site of occurrence in subjects with OSCC, no significant difference in the mean levels of serum MMP-2 was observed.…”
Section: Discussionsupporting
confidence: 87%
“…MMP-2 has been detected in serum of breast cancer, prostate cancer, colorectal cancer, and laryngeal cancer patients. [10][11][12][13] Serum MMP-2 levels have been found to be increased in them as compared to the control group.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Numerous studies have revealed that MMPs are overexpressed in several types of malignant tumours, including oral cancer [6–8]. Of the MMPs, MMP-2 and MMP-9, known as the gelatinases that degrade the main constituent of the basement membrane and type IV collagen, have been recognised as crucial in cancer invasion and metastasis.…”
Section: Introductionmentioning
confidence: 99%